The study of the level of commitment to prayer and the level of anxiety in the students of Nursing and Midwifery Faculty in Sanandaj city and its relation to their demographic characteristics in 2009 - Farzaneh Zaheri; Simin Nazarian; Sirous Shahsawari (Kurdistan University of Medical Sciences, 2016)
Background and Aim: man may experience different anxieties and stresses during his life and overcoming them decreases his spiritual and mental strength. This could lay the ground for dangerous mental and physical diseases. Man could increase his mental power in the light of continuous prayer. This study aimed to study the level of commitment to prayer and the level of anxiety in the students of Nursing and Midwifery Faculty at Kurdistan University of Medical Sciences and its relation to their demographic characteristics in 2009. Materials and Methods: In this cross-sectional study, 182 students of the faculty of Nursing and Midwifery were selected by census method. Data collection was conducted by demographic information and the standard Zong anxiety questionnaire. SPSS16 was used for data analysis. Moreover, descriptive statistics (Frequency percent), chi-square tests and t-test were used. Findings: According to the results, the anxiety score of (7.85 %) of the students was normal, while (6.12%) had mild anxiety and (6.1%) had moderate anxiety. Only (3.70%) had said prayer and no significant relationship was observed (p= 0.240) between level of anxiety and field of study, living in the dormitory, marital status, educational level and saying prayer.  Conclusion: The results of this study indicated that about (2.14%) of the college students had some degrees of anxiety. Since the majority of the subjects had a history of saying prayer. Therefore, prayer is probably one of the reasons for low anxiety.